Customer Loyalty Model of Export Product Shipment Certification - Lubis, Muchdy; Hartoyo, Hartoyo; Zulbainarni, Nimmi (Universitas Bina Sarana Informatika, 2025)
This paper investigates the loyalty model of customers towards a certification governing body for export product shipment certification. The present study investigates the impact of service quality, consumer satisfaction, customer trust, and customer loyalty on the established model. The model will be used to determine the specific areas that need enhancement to improve consumer loyalty. There were 104 participants took part in the study by means of convenience sampling and telephone questionnaire surveys. This study results that customer satisfaction is greatly influenced by the five components of Servqual service quality: tangibility, empathy, dependability, responsiveness, and assurance. Moreover, it was shown that the five categories of service quality had a substantial impact on customer trust. The level of product satisfaction and trust directly influences the loyalty of customers. In addition to examining direct effects, the study also detected indirect effects resulting from mediating variables. The findings indicate that consumer trust is influenced by reliability through customer satisfaction, and customer trust is influenced by assurance through customer satisfaction. Consumer satisfaction, in turn, influences consumer loyalty by means of customer trust. Managerial implication of this study encompasses the instruction of personnel in export product certification services, including areas such as communication, regulations, document control, and management of personal protective equipment. The organization is advised to establish a systematic service evaluation process and then execute a follow-up strategy to guarantee that the evaluation findings are acted upon.